English Written Test: UMP Scholarship 2023 - Fathiah Izzati, Mohammad Fadzillah (UMPSA, 2023)
19 April 2023 - In a bid to enhance language proficiency and academic excellence, the prestigious Universiti Malaysia Pahang (UMP) has announced the inclusion of an English Written Test as part of its scholarship selection process for the year 2023.